Delta-Sigma Modulators : Modeling, Design and Applications. (World Scientific, 2003)
This important book deals with the modeling and design of higher-order single-stage delta-sigma modulators. It provides an overview of the architectures, the quantizer models, the design techniques and the implementation issues encountered in the study of the delta-sigma modulators. A number of applications are discussed, with emphasis on use in the design of analog-to-digital converters and in frequency synthesis. The book is education- rather than research-oriented, containing numerical examples and unsolved problems. It is aimed at introducing the final-year undergraduate, the graduate stu.